2019
DOI: 10.1177/1464419319895351
|View full text |Cite
|
Sign up to set email alerts
|

A novel motion cueing algorithm integrated multi-sensory system–Vestibular and proprioceptive system

Abstract: Motion cueing algorithms are used to produce a motion which feels as realistic as possible while remaining in the limited workspace of driving simulators. Several optimal motion cueing algorithms were developed to improve both the exploitation of the workspace of a driving simulator and the realistic of the simulated motion. In the dynamics model of the optimal motion cueing algorithms, several kinds of motion-sensory systems are integrated to optimize the simulated motion sensation. However, most previous wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…OpDA showed to have a good response which tracks the target lateral specic force, decreases the false cues of angular velocity, and reduces the negative cues of head-tilted-angle. A comparison study shown in [22] illustrates that OpDA outperforms some of the current MCAs and oers performance at a level close to that of the MPC algorithm.…”
Section: Opda Algorithmmentioning
confidence: 85%
See 2 more Smart Citations
“…OpDA showed to have a good response which tracks the target lateral specic force, decreases the false cues of angular velocity, and reduces the negative cues of head-tilted-angle. A comparison study shown in [22] illustrates that OpDA outperforms some of the current MCAs and oers performance at a level close to that of the MPC algorithm.…”
Section: Opda Algorithmmentioning
confidence: 85%
“…This paper categorized these robotic machines based on their working principles and the number of DoF that they provide to facilitate smooth translational and rotational positioning in the 3d space. Furthermore, the Adaptive washout lter [6], [18][21] Optimal washout lter [22] OpDA algorithm [23] Sliding mode-based cueing [24][26], [31] Model predictive control [27] [29] Time-varying model predictive control [30], [32] Nonlinear model predictive control [33] Neural network [34] Fuzzy control system…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal MCA for vehicle driving simulators that incorporate driver's body and perception models is proposed so as to include human body vibrations [15,[28][29][30]. Human vibrations are of three types: the mass-spring-damper model [31], the model from the finite element method [32], and the transfer function model [14].…”
Section: Proposed Methodologymentioning
confidence: 99%
“…They consist of scaling, filtering and tilt-coordination and became a reference widely used in the field because of their relative simplicity and reasonable performance. [11] have proposed other strategies such as MCA based on Optimal Control which integrate a mathematical model of the human vestibular system. In [12] [13], a Model Predictive Control (MPC) has been proposed in order to improve the realism of motions produced by the platform, taking into account its workspace, where the algorithm parameters are set for the worst case scenario.…”
Section: Simulator Motion Cuesmentioning
confidence: 99%